CERN LHC signals for a neutrino mass model with bilinear R-parity violating minimal anomaly mediated supersymmetry - De Campos, F. [UNESP]; Díaz, M. A.; Iboli, O. J.P.; Magro, M. B.; Porod, W.; Skadhauge, S. (American Physical Society (APS), 2008)
We investigate a neutrino mass model in which the neutrino data is accounted for by bilinear R-parity violating supersymmetry with anomaly mediated supersymmetry breaking. We focus on the CERN Large Hadron Collider (LHC) phenomenology, studying the reach of generic supersymmetry search channels with leptons, missing energy and jets. A special feature of this model is the existence of long-lived neutralinos and charginos which decay inside the detector leading to detached vertices. We demonstrate that the largest reach is obtained in the displaced vertices channel and that practically all of the reasonable parameter space will be covered with an integrated luminosity of 10fb-1. We also compare the displaced vertex reaches of the LHC and Tevatron. © 2008 The American Physical Society.